Differences in principals’ experience on their instructional leadership behaviours in colleges of education in Ghana: Differences in principals’ experience on their instructional leadership behaviours in colleges of education in Ghana (Journal of Educational Management, 2021)
The study assessed the differences in Principals’ instructional leadership behaviours based on experiences (number of years served as Principal) in Colleges of Education (CsOE) in Ghana using the descriptive survey design. The population of the study was all Principals from the forty-two (42) CsOE in Ghana. The study sampled thirty-six (36) Principals using the simple random sampling technique. The Principal Instructional Leadership Behaviours (PILB) scale was used to collect data. Means, standard deviations and the one-way ANOVA were used to analyse the research question and to test for the hypothesis respectively. The study revealed that Principals often promote collaboration among tutors, provide support for tutors’ work, provide an induction for new tutors and promote in-service training for tutors in CsOE in Ghana. However, the findings from the study gleaned that supervision of instruction was sometimes exhibited by Principals in CsOE in Ghana. The study further found that Principals’ instructional leadership behaviours differed when they were grouped according to their experience. It was concluded that though Principals provide instructional leadership for the benefit of tutors and the general teaching and learning climate of CsOE in Ghana, their instructional supervision should be improved. The study yielded a central recommendation that Principals of CsOE need to improve upon their supervision of instruction to promote the continuous professional development of tutors.
Keywords: instructional leadership behaviours; principals’ experience; colleges of education